Smallholder dairy farmers’ access to modern milk marketing chains in India - Kumar, Anjani; Staal, Steven J.; Singh, D.K. (2011)
The smallholder dairy farmers’ access to modern milk marketing chain has been assessed in India by collecting data at the farm level in two states, viz. Bihar and Punjab. These states are among the largest milk producing states of the country but depict stark variations in terms of milk productivity and per capita milk availability. Another significant feature is the emergences of modern milk marketing chains in both the states. The study has shown that in spite of the growing presence of modern milk supply chains, the traditional milk supply chain is still dominant in the Indian milk market. Its presence is even more pronounced in less-developed states like Bihar. However, the traditional milk supply chain is being replaced, albeit slowly, with the commercialization of dairying. The structure of the milk marketing in Punjab has depicted this conclusion. The study has concluded that the modern milk supply chain seems to have an inclusive structure and the resource-poor dairy farmers are not excluded from the modern milk supply chain. The study has argued that the traceability and food safety issues will further strengthen the modern milk supply chain. The scalability of the modern milk supply chain will depend on the development of milk collection and transportation facilities and incentive pricing for a quality produce.